The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/fuels2040030
|View full text |Cite
|
Sign up to set email alerts
|

Mixotrophic Cultivation of Microalgae in Cassava Processing Wastewater for Simultaneous Treatment and Production of Lipid-Rich Biomass

Abstract: Cassava processing wastewater (CPW) is a highly polluting, liquid residue of cassava processing, usually discarded or treated anaerobically. However, it can serve as a low-cost culture medium for microalgae. After a preliminary evaluation of the growth of 10 microalgal strains in diluted CPW, the microalgae Haematococcus pluvialis SAG 34−1b and Neochloris (Ettlia) oleoabundans UTEX 1185 were selected for cultivation in CPW without a supply of additional nutrients and evaluated for their growth, lipid productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…They rely on organic chemicals found in the media [52]. Sorgatto, Soccol, Molina-Aulestia, de Carvalho, de Melo Pereira, and de Carvalho [53] reported that microalgae grew faster in cassava wastewater and produced lipids similar to synthetic mixotrophic cultures. Another research by Nwanko and Agwa (2021) showed that the optimal ratio of cassava peel water to cassava wastewater (CP:CW) for growth was 160:40.…”
Section: Cassava Wastewater As a Substrate For Microalgaementioning
confidence: 99%
See 1 more Smart Citation
“…They rely on organic chemicals found in the media [52]. Sorgatto, Soccol, Molina-Aulestia, de Carvalho, de Melo Pereira, and de Carvalho [53] reported that microalgae grew faster in cassava wastewater and produced lipids similar to synthetic mixotrophic cultures. Another research by Nwanko and Agwa (2021) showed that the optimal ratio of cassava peel water to cassava wastewater (CP:CW) for growth was 160:40.…”
Section: Cassava Wastewater As a Substrate For Microalgaementioning
confidence: 99%
“…Over 99% of ammonia, nitrites, and nitrates, could be reduced. [ microalgae in wastewater [53,61]. Table 3 depicts the cassava wastewater treatment product based on microalgae.…”
Section: Arthrospira Platensismentioning
confidence: 99%
“…Currently, processes such as filtration, flocculation, and sterilization are also being evaluated as pretreatment for this effluent. However, the most promising current research is using the anaerobic digestion of CPW [17,94]. After pretreatment, the effluent CPW (or its digestate) still contains high amounts of nitrogen, phosphate, and soluble sugars, thus allowing the mixotrophic or heterotrophic microalgae production for bioproducts, such as biomass, biodiesel, or pigments [95].…”
Section: Cpw Cassava Processing Wastewatermentioning
confidence: 99%
“…By providing nutrients at a meager cost, using residues can reduce expenses in algal production. This is advantageous for already established products, such as PC (phycocyanin, a blue-colored protein from cyanobacteria) and AX (astaxanthin, a carotenoid), and enables the production of new products, such as biofuels and PHAs (polyhydroxyalkanoates, biopolymers produced by some cyanobacteria) [16][17][18]. Some bottlenecks to the massive production of microalgal biomass, such as the low cell concentration in cultures and the consequent need for large cultivation areas and large volumes of culture media and nutrients, can be solved using agro-industry wastewaters.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the remediation setup with cassava starch introduced had the lowest water TPH concentration (223 mg/L) at the end of the experimental period. Sorgatto et al (2021) reported that cassava starch in solution helps in the growth of aquatic microscopic plants. These microscopic plants carry out phytoremediation, which lowers the water's TPH content, and reduces its biological oxygen demand and its chemical oxygen demand.…”
Section: Impact Of Remediating Therapy On the Water Tphmentioning
confidence: 99%